Relationship of Trochlear Morphology and Patellofemoral Joint Alignment to Superolateral Hoffa Fat Pad Edema on MR Images in Individuals with or at Risk for Osteoarthritis of the Knee: The MOST Study - Widjajahakim, Rafael (Radiology, 2017)
PURPOSE: To determine the relationship of patellofemoral joint alignment and trochlear morphology to superolateral Hoffa fat pad (SHFP) edema on magnetic resonance (MR) images in older adults with or at risk for osteoarthritis of the knee. MATERIALS AND METHODS: Institutional review board approval and written informed consent were obtained from all subjects. The Multicenter Osteoarthritis Study is a prospective cohort study of older adults with or at risk for osteoarthritis of the knee. Subjects were recruited from Birmingham, Alabama, and Iowa City, Iowa. In this cross-sectional study, patellofemoral joint alignment (bisect offset, patellar tilt angle, and Insall-Salvati ratio), trochlear morphology (sulcus angle, lateral and medial trochlear inclination, and trochlear angle) and SHFP edema were assessed on MR images of the knee. Measures of alignment and morphology were divided into quartiles, and SHFP was determined to be present or absent. Separate logistic regression models were used to determine the relationship of each measure of alignment and morphology to the presence of SHFP edema, with adjustments for age, sex, and body mass index. RESULTS: SHFP edema was present in 152 (13.4%) of the 1134 knees that were included. When compared with knees with measurements in the lowest quartile, knees with measurements in the highest quartile for trochlear angle, bisect offset, and Insall-Salvati ratios were 1.6 (95% confidence interval [CI]: 1.0, 2.6), 2.3 (95% CI: 1.3, 4.0), and 8.9 (95% CI: 4.7, 16.9) times more likely to show SHFP edema, respectively. No relationship was found between other measures and SHFP edema. CONCLUSION: A more anterior trochlear facet, a more laterally displaced patella, and knees with patella alta were significantly associated with SHFP edema on MR images in subjects with or at risk for osteoarthritis of the knee. (©) RSNA, 2017